CONSAL X BBQ and a night of batik extravaganza, 22 May, 1996, Perpustakaan Negara Malaysia - Congress of Southeast Asian Librarians [videorecording] (10th : 1996 : Kuala Lumpur); CONSAL X ( videorecording) (Kuala Lumpur : Perpustakaan Negara Malaysia, 1996)
A videorecording of the barbecue and fashion show during one of the nights in CONSAL X, 1996, Kuala Lumpur
Title from data sheet
Keywords: Fashion shows; Batik -- Malaysia; Librarians